SCHOOL FACILITY AND MANAGEMENT IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW OF AVAILABILITY, CHALLENGES AND SUSTAINABILITY - M. Naufal Athallah; Yulia Tri Samiha; Asri Karolin; Kasinyo Harto; Amalia Hasanah (Jurnal Konseling Pendidikan Islam, 2026)
School facility play an important role in supporting educational quality, student wellbeing, and learning effectiveness. However, challenges related to the availability, management, and sustainability of educational facilities remain evident in many Indonesian school. This study aims to systematically review previous studies on school facility availability and management in Indonesia using the Systematic Literature Review (SLR) approach. The review followed the PRISMA framework through the stages of identification, screening, eligibility, and inclusion. Literature searches were conducted using four databases, namely Scopus, Google Scholar, ERIC, and ProQuest. A total 0f 12 studies underwent the quality appraisal process using an adapted version of the Critical Appraisal Skills Programme (CASP) checklist, in which three low-quality studies were excluded, resulting in nine studies in the final thematic synthesis. The findings indicate that school facilities in Indonesia continue to face challenges related to infrastructure disparities, inadequate sanitation and learning facilities, weak maintenance practices, and disaster-related vulnerabilities, particularly in border, disaster-prone, and underserved areas. The review also reveals that school facility management practices remain largely operational and fragmented, focusing primarily on maintenance, utilization, supervision, and budgeting process. In addition, school facilities were found to influence students’ learning experiences, well-being, literacy engagement, and participation in educational activities. Overall, this study highlights the importance of strengthening sustainable facility management systems, equitable infrastructure development, and resilience-oriented educational policies to support safe, inclusive, and effective learning environments in Indonesia.